The Effect of Tax Knowledge, Quality of Fiscal Service, and Implementation of Taxpayer E-Filling on Taxpayer Compliance: Pengaruh Pengetahuan Perpajakan, Kualitas Pelayanan Fiskus, Dan Penerapan E-Filling Wajib Pajak Terhadap Kepatuhan Wajib Pajak - Zia Vawzia Lazul Varis; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2021)
Tax compliance is an attitude of submission or obedience in which the taxpayer fulfills all obligations and exercises rights in taxation. This study aims to examine what are the factors that influence taxpayer compliance by using the variables of tax knowledge, quality of tax service, and the application of taxpayer e-filing. Collecting data in this study using a questionnaire. The regression model used in this study is a multiple linear regression model with the help of the SPSS program. The research sample was selected using a simple random sampling method as many as 50 taxpayers. The results showed that only the tax knowledge factor and the quality of tax service quality had a positive and significant effect on taxpayer compliance, while the e-filling implementation factor had a negative and insignificant effect on taxpayer compliance.